2021
DOI: 10.4317/medoral.24736
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated whole salivary flow rate: The most appropriate technique for assessing salivary flow in Sjögren syndrome

Abstract: Background We sought to determine the most appropriate method for measuring salivary flow to aid the diagnosis of Sjögren's syndrome (SS). Specifically, we compared the unstimulated whole salivary flow rate (UWSFR) with the stimulated whole salivary flow rate (SWSFR). Material and Methods This case-control study comprised one group of 103 patients with SS and a control group of 50 healthy people. We measured the UWSFR and SWSFR in both groups according to the guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…These results, therefore, are in accordance with the most recent criteria for the SS diagnosis 27 and the ones proposed by Vitali et al, 14 which only consider the UWS flow for the diagnosis of SS. Some authors, 28 24 These authors reported a negative significant correlation between UWS levels and VAS scores for xerostomia. In the present study, this correlation between UWS flow rate and total VAS score for xerostomia was positive and statistically significant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results, therefore, are in accordance with the most recent criteria for the SS diagnosis 27 and the ones proposed by Vitali et al, 14 which only consider the UWS flow for the diagnosis of SS. Some authors, 28 24 These authors reported a negative significant correlation between UWS levels and VAS scores for xerostomia. In the present study, this correlation between UWS flow rate and total VAS score for xerostomia was positive and statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…These results, therefore, are in accordance with the most recent criteria for the SS diagnosis 27 and the ones proposed by Vitali et al, 14 which only consider the UWS flow for the diagnosis of SS. Some authors, 28 however, have argued that the UWS can be influenced by factors, such as the age, use of medications, etc., and have proposed the use of SWS flow as a more reliable method of assessing the glandular function in pSS. The present research has analyzed how different levels of salivary flow rates may influence the OHIP‐14 in pSS.…”
Section: Discussionmentioning
confidence: 99%
“…Acid stimulation method Place a solution of 2% citric acid on each side of the tongue every 30 seconds for five minutes and collect saliva [21] Get more saliva in a short time [31] Change the composition of saliva [25] Change salivary pH [25] Need collaboration [25] Chewing method Collect saliva after chewing an unflavored gum base or paraffin wax [21] Get more saliva in a short time [31] Change the composition of saliva [25] Change salivary pH [25] Uncontrollable chewing force and force duration [32] Major salivary gland Parotid gland Place the Lashley cup at the mouth of the parotid gland catheter to collect saliva from the parotid gland [32] Not invasive [25] Time-consuming [33] Complex procedure [33] Required skilled personnel [33] Submandibular gland and sublingual gland Use a Wolff saliva collector to collect saliva from the submandibular and sublingual gland [32] Not invasive [33] Time-consuming [33] Complex procedure [33] Require skilled personnel [33] Table 1: Continued.…”
Section: Stimulated Whole Saliva [Sws]mentioning
confidence: 99%
“…Paraffin wax or chewing gum are used as stimuli for collecting saliva through induction of masticatory action, leading to an increased salivary flow rate. Effectively collecting saliva in patients with SS is difficult because the saliva flow rate is significantly decreased in those with the disease [ 7 , 8 ]. Therefore, a considerable length of time is required to collect an appropriate amount of saliva, which can negatively affect the quality of the sample [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effectively collecting saliva in patients with SS is difficult because the saliva flow rate is significantly decreased in those with the disease [ 7 , 8 ]. Therefore, a considerable length of time is required to collect an appropriate amount of saliva, which can negatively affect the quality of the sample [ 8 ]. As such, many studies investigating SS have used stimulated saliva as a sample, although such stimuli can affect the quantity and pH of saliva.…”
Section: Introductionmentioning
confidence: 99%